Choreography as Decolonial Practice: Aesthetics of Piety and Modernity in West Sumatra’s Musabaqah Tilawatil Qur’an Competitions - Katia Chaterji; Susas Rita Loravianti (Department of Anthropology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This article explores two dance choreographies, Menghimpun Cahaya (Gathering Light) and Ziarah Surau Kota Hujan (Pilgrimage to the City of Rain’s Prayer Hall), performed at the opening ceremonies of West Sumatra’s Qur’anic recitation competitions (Musabaqah Tilawatil Qur’an, or MTQ) in 2019 and in 2021. While the MTQ have been studied as sites of performing piety, nationalism, and/or “goodness”; this article explores the role of choreography in articulating performative claims about Islamic knowledge production, cultural authority, and locally rooted constructs of modernity. Focusing on the MTQ as religious and political event, this article considers how choreographic practice shapes the construction of tradition and asserts the performing arts as a critical arena in which Minangkabau artists define their relationships to the past, present, and future of Muslim cultural identity. This article is in conversation with debates to decolonize performing arts and choreography through consideration of collaboration and autoethnography.